Case Series of HIV Infection-Associated Arteriopathy: Diagnosis, Management, and Outcome over a 5-Year period at Maharaj Nakorn Chiang Mai Hospital, Chiang Mai University - Saritphat Orrapin (2018)
© SAGE Publications. Patients infected with human immunodeficiency virus (HIV) can present with 4 pathology types: drug-induced vasospasm (ergotism), arterial limb ischemia, critical limb ischemia, and aneurysm. Although these problems are common vascular problems, they result in increased morbidity and mortality in HIV-infected patients, especially aneurysm. Patients with these problems tend to be diagnosed with difficulty because of atypical symptoms and signs. Because of lack of data in treatment outcome literature, our report explores and provides information on HIV infection-related arteriopathy. There were 17 patients in our 5-year review. There was no death in patients except the aneurysm type. The survival of aneurysm patients was significantly lower than from other pathologies (P =.003). Our case series showed good short-term outcome, and patients were not at risk for less beneficial surgical procedures.